PERAN ARTIFICIAL INTELLIGENCE DALAM MANAJEMEN OPERASIONAL: PENDEKATAN INOVATIF UNTUK PENINGKATAN EFISIENSI DAN PRODUKTIVITAS - Rosalina Siagian; Zahara Tussoleha Rony (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
Artificial Intelligence (AI) has become an essential tool in enhancing efficiency and productivity in operational management. This technology enables process automation, rapid data processing, and supply chain optimization. While AI can accelerate production, reduce human error, and improve product quality, its implementation requires significant investment in infrastructure and human resource training. Additionally, other challenges faced by companies include workforce resistance to automation, ethical issues in decision-making, and potential vulnerability to cyberattacks. This study aims to analyze AI’s contribution to improving efficiency, identify the challenges faced by companies, and explore its impact on the workforce. By addressing these challenges, companies can leverage AI to gain a sustainable competitive advantage.